Drifts of myths. Mythological discourses of Mieczysław Jastrun and Zbigniew Herbert - Cezary Zalewski (Przestrzenie Teorii)
This article deals with M. Jastrun’s and Z. Herbert’s essays in which mythological figures (Minotaur, Iphigenia) appear. Demythologisation strategies of both authors are presented, which consist in either direct or indirect (most often ironic) questioning of sacrificial rites. Mythological murders are deprived of their primary, ritual justification, becoming an expression of unjustified and collective aggression.